Neutron tomography of porous aluminum electrodes used in electrocoagulation of groundwater - Jang, G. G.; Zhang, Y.; Keum, J. K.; Bootwala, Y. Z.; Hatzell, M. C.; Jassby, D.; Tsouris, C. (Frontiers in Chemical Engineering, 2022)
In this work, neutron computed tomography (CT) is employed to investigate the dissolution of porous aluminum electrodes during electrocoagulation (EC). Porous electrodes were chosen in efforts to reduce electric power requirements by using larger surface-area electrodes, having both inner and outer surface, for the EC process. Neutron CT allowed 3D reconstruction of the porous electrodes, and image analysis provided the volume of each electrode vs thickness, which can indicate whether the inner surface is effectively involved in EC reactions. For the anode, the volume decreased uniformly throughout the thickness of the electrode, indicating that both the outer and inner surface participated in electrochemical dissolution, while the volume of the cathode increased uniformly vs thickness, indicating deposition of material on both the outer and inner surface. The attenuation coefficient vs thickness, increased for both anode and cathode, indicating surface chemistry changes. For the anode, the attenuation coefficient increased slightly but uniformly, probably due to aluminum oxide formation on the surface of the anode. For the cathode, the attenuation coefficient increased more than for the anode and nonuniformly. The higher increase in the attenuation coefficient for the cathode is due to precipitation of aluminum hydroxide on the electrode surface, which added hydrogen. Image analysis also showed that, although the attenuation coefficient increased throughout the thickness of the electrode, most of the hydroxide deposition occurred on the outer surface. Energy analysis showed that porous electrodes can be used to reduce process energy requirements by as much as 4 times compared to solid electrodes.